Alteration of light-dependent gene regulation by the absence of the RCO-1/RCM-1 repressor complex in the fungus Neurospora crassa - Ruger-Herreros, Carmen; Gil-Sánchez, María del Mar; Sancar, Gencer; Brunner, Michael; Corrochano, Luis M. (PLOS ONE, 2014)
The activation of transcription by light in the fungus Neurospora crassa requires the White Collar Complex (WCC), a photoreceptor and transcription factor complex. After light reception two WCCs interact and bind the promoters of light-regulated genes to activate transcription. This process is regulated by VVD, a small photoreceptor that disrupts the interaction between WCCs and leads to a reduction in transcription after long exposures to light. The N. crassa RCO-1/RCM-1 repressor complex is the homolog of the Tup1-Ssn6 repressor complex in yeast, and its absence modifies photoadaptation. We show that the absence of the RCO-1/RCM-1 repressor complex leads to several alterations in transcription that are gene-specific: an increase in the accumulation of mRNAs in the dark, a repression of transcription, and a derepression of transcription after long exposures to light.
Gesehen am 25.09.2020